Studies in the semiotics of biblical law - Jackson, Bernard S. (Journal for the study of the Old Testament. Supplement series, 2000)
This book explains and illustrates a variety of semiotic issues in the study of biblical law. Commencing with a review of relevant literature in linguistics, philosophy, semiotics and psychology, it examines biblical law in terms of its users, its medium and its message. It criticizes our use of the notion of 'literal meaning', at the level of both words and sentences, preferring to see meaning constructed by the narrative images that the language evokes. These images may come from either social experience or cultural narratives. Speech performance is important, both in the negotiation of the.